Formative observation of teaching: focusing peer assistance on teachers' developmental goals. Issue 6 (18th August 2017) - Drew, Steve; Phelan, Liam; Lindsay, Katherine; Carbone, Angela; Ross, Bella; Wood, Kayleen; Stoney, Susan; Cottman, Caroline
Abstract: Peer observation of teaching can provide valuable insights into effective educational practices. By adopting a developmental focus, peer observation can also provide insights into how practices might be enhanced and, importantly, how enhancements in practices might be aligned to teachers' development goals. However, a review of peer observation of teaching undertaken at Australian universities demonstrates that observation instruments and protocols typically do not explicitly afford alignment of peers' observations with teachers' developmental goals. Analysis of observers' uses of popular peer observation instruments through the deployment of the Peer Assisted Teaching Scheme through multiple institutions across Australia has informed the development and trial of a novel observation instrument and protocol design that is aligned with observer use characteristics, and provides a focus on development goals. This study will be of interest to teachers and academic developers researching and implementing goal-oriented curricular and pedagogical development through peer observation.